Cross-cultural adaptation and validation of the cooking task to the French-Canadian context: assessing the impact of executive function disorders through cooking activities. - Crépeau-Hubert, Frédérik; Baril, Audrey Changya; Di Caprio, Sofia; Haddad, Dahlia; Picq, Christine; Poncet, Frédérique (Disability & Rehabilitation, 2024)
Acquired brain injury (ABI) often leads to deficits in executive functioning (EF) which is responsible for severe and longstanding disabilities in activities of daily living. The "Cooking Task" (CT), an ecological test of EF involving multi-tasking, was developed in France and exhibits excellent psychometric properties but has not yet been adapted and validated for the French-Canadian context. Conduct a cross-cultural adaptation and validation of the CT for the French-Canadian context. The CT was translated and adapted by a committee of experts and was validated. Adaptation-changes were made to the language (e.g., cartable vs classeur), the materials (e.g., measuring cup vs scale), and the measuring units (e.g., ml/cups vs grams). Validation-Preliminary analyses were conducted on 24 participants with an ABI and 17 controls. Construct convergent validity: The French-Canadian-CT discriminates between ABI and control total score on the CT and on most error type categories. Construct known-group validity: French-Canadian-CT scores correlated with another measure of EF deficits (Dysexecutive Questionnaire and Six Elements Task). Inter-rater reliability score for the total error was high (ICC=.84) and results were similar to those obtained for the France-CT. This study will provide a new ecologically valid tool for clinicians in Canada. Acquired brain injury often leads to deficits in executive functioning which is responsible for severe and longstanding disabilities in activities of daily living. Ecological assessments are used to evaluate the impact of executive function disorders on activities of daily living. The "Cooking Task" (CT), an ecological test of EF involving multi-tasking, exhibits excellent psychometric properties. The adaptation and validation of the Cooking Task in Canadian French will provide a new measurement tool for occupational therapists in Canada (French-speaking OT or French-speaking patient).